Three challenges for the future development of the information society in Europe - Marc Bogdanowicz; Clara Centeno; Jean-Claude Burgelman (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
This paper is based on past and current research about Information Society developments in an Enlarged Europe, and in particular in the New EU Member States and the Candidate Countries, carried out at the Institute for Prospective Technological Studies, a research institute of the Joint Research Centre Directorate General of the European Commission. The research aimed at understanding and identifying Information Society strategies for the European countries that would support their economic and social development towards the socalled European Lisbon objectives. This paper presents some of the conclusions of this work, by focusing on one of its achievements: the identification of ten past determinants and three future challenges for Information Society developments in and Enlarged Europe.
Keywords: 330; Wissensgesellschaft; EU-Mitgliedschaft; EU-Staaten